Subcutaneous immunotherapy with depigmented‐polymerized allergen extracts: a systematic review and meta‐analysis. Issue 1 (5th June 2019) - Mösges, Ralph; Valero Santiago, Antonio; Allekotte, Silke; Jahed, Nilufar; Astvatsatourov, Anatoli; Sager, Angelika; Sánchez‐López, Jaime
Abstract: Background: Double‐blind, placebo‐controlled trials (DBPCTs) have confirmed the efficacy of allergen‐specific immunotherapy (AIT) with depigmented‐polymerized allergen extracts (DPAEs). This systematic review evaluates the efficacy of AIT using different allergens in different severity stages of rhinoconjunctivitis with or without asthma in the pollen studies and asthma and rhinitis in the house dust mite studies in comparison to placebo. Methods: We used MEDLINE, Embase, CENTRAL and LILACS databases to review DBPCTs published until July 2016. The combined symptom and medication score (cSMS) served as primary endpoint. The total rhinoconjunctivitis symptom score (RCSS) and total score in Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) were secondary efficacy endpoints. Solicited local and systemic adverse events were secondary safety endpoints. We assumed a random effects model with standardized mean differences (SMDs) or mean differences as summary statistics. In a subgroup analysis, we classified the studies following the GINA (Global Initiative for Asthma) and ARIA (Allergic Rhinitis and its Impact on Asthma) guidelines for rhinoconjunctivitis and asthma severity. Results: Six DBPCTs in pollen and 2 trials in house dust mites (HDM) were selected. Patients (N = 915) with intermittent or mild persistent asthma were included in 3 (37.5%) and 5 (62.5%) trials, respectively. Two (25%) HDM studies included patients with moderate persistent asthma, 4 trials patients with moderate‐to‐severe rhinoconjunctivitis. Treatment periods ranged from 12 to 24 months. AIT with DPAEs yielded significantly lower cSMS (SMD: 1.9, 95% CI: 0.9–2.8) and RQLQ (SMD: 0.3, 95% CI: 0.1–0.5) values than did placebo. An exploratory analysis of cSMS and RCSS suggested that the efficacy of AIT treatment with DPAEs was higher in trials including patients with more severe rhinoconjunctivitis and asthma. A publication bias was not detected. Heterogeneity between individual studies was explained by differences in severity. Patients receiving DPAEs did not experience a significantly higher risk of local (OR: 1.55, 95% CI: 0.86–2.79) or systemic reactions (OR: 1.94, 95% CI: 0.98–3.84). Conclusions: Compared to placebo, AIT with DPAEs is effective in patients with pollen‐ or HDM‐induced rhinoconjunctivitis with or without allergic asthma and improves health‐related quality of life. It does not differ significantly in safety and tolerability.